Effect of supine and prone flexion positions on heart rate, oxygen saturation, and pain score of preterm infants - Çağlayan, Sabiha; Gözen, Duygu (Erciyes University School of Medicine, 2021)
Objective: The study aimed to determine the effect of supine and prone flexion positions on heart rate, oxygen saturation, and pain level of preterm infants in the neonatal intensive care unit.Materials and Methods: This study consisted of 46 preterm infants in a university hospital between February and November 2014. The effects of two different positions on heart rate, oxygen saturation, and pain were assessed by giving both positions to each infant for 2 h.Results: Heart rate increased in the prone flexion position, but oxygen saturation was similar in both positions. In addition, pain score decreased on the second hour in prone position.Conclusion: The results showed that infants were influenced more by environmental stimuli in thesupine flexion position.
Keywords: Neonatal Intensive Care; Prone Positioning; Flexion Positioning